INTRODUCTION TO UPDHATU AND FORMATION OF STANYA FROM RASADHATU (AYUSHDHARA, 2020)
Ayurved is a healing science based on the studies and keen observations. Ayurved gives priority to maintain the healthy state of a normal human being and treat the disease of patient. Success of any science depends on its fundamental principles. Fundamentals of Ayurved are very important body elements such as Dosha, Dhatu, Mala and Agni. Ayurved explained about quantities assessment of various biological elements like normal height of a person, normal values of different body tissues (Dhatu) like Rasa (plasma), Rakta (blood) etc. Updhatu is subsidiary tissue arises from Dhatus. Stanya (breast feeding) is one of them which is derived from Rasa Dhatu. World Health Organization recommends that exclusive breastfeeding for the first six months of life, after which "infants should receive nutritionally adequate and safe complementary foods. So in this article an attempt has been made to understand the concept of Updhatu and formation of Stanya from Rasa Dhatu. For this study, the basic materials have been collected from the Ayurved classics as well as textbook of contemporary modern medical science have been referred for better understanding of the concept and its comparison with contemporary science.